Pengembangan Modul Berbasis PjBL (Project Based Learning) pada Materi Virus untuk Meningkatkan Minat Belajar Siswa Kelas X - Herman Jufri Andi; Zainurrahman Zainurrahman; Faizil Muqoddas; Lukluk Ibana; Syaiful Bahri (Universitas Palan, 2024)
Development Module is the process of creating or refining an educational module. This module can consist of lesson materials, study guides, or learning packages designed to achieve specific learning objectives. A good learning module is usually organized systematically, refers to competency standards, and uses various engaging learning media. This research uses the Research and Development (R&D) method conducted at SMA Darun Najah.The purpose of the research is to increase students' interest in learning. The research results show that the PjBL-based module can enhance students' interest in learning. This was determined by giving a questionnaire to students containing several questions, and the students' responses indicated that the module could boost their enthusiasm for learning.